Análise da satisfação do Franchising para com a fraqueadora: um estudo de caso no ramo de seguros - Chitolina, Tânia Mara (2020)
This paper was developed looking forward understanding the business relationships between a franchisor and its franchisees, in the field of insurances, analyzing the degree of satisfaction of these franchisees. The methodology used in its construction was exploratory and descriptive, carried out through a case study, with quantitative and qualitative data analysis. The data were collected through the application of a semi-structured questionnaire, composed of open, dichotomous and a five-point Likert scale questions. The questionnaire was built on the Google Forms® platform and sent to 31 franchisees, with a response rate of 83.87%. The results obtained showed that the majority of franchisees are satisfied to a moderate degree. A relationship between the manager's experience and the return on investment was percived. Dissatisfactions, although scarce, were directly related to the recent time of activities and the economic slowdown during the COVID-19 pandemic in 2020.